HISTORICAL FOUNDATIONS OF ROAD DEVELOPMENT, CONSTRUCTION OVERSIGHT, AND ANTI-CORRUPTION MEASURES (World Bulletin of Management and Law, 2025)
The article analyzes the historical stages of road development, road construction in ancient states, systems of control and accountability, efforts to combat the embezzlement of state property in the Roman Empire, and mechanisms for overseeing road construction quality in Central Asian civilizations, particularly during the era of Amir Timur and the Timurids. It also highlights the development of road infrastructure in the territory of Uzbekistan, caravan routes, and the distinctive features of the control and investigation system during the Timurid period. The scientific analyses are interpreted in relation to historical sources, ancient legal codes, and modern road construction theories